Sebaran Batuan Daerah Panas bumi Terak Bangka Tengah berdasarkan Anomali Magnetik - Alawiyah, Umi; Kusmita, Tri (Jurnal Riset Fisika Indonesia, 2022)
Geothermal potential in Indonesia has various non volcanic geothermal sources, one of which is geothermal in the Terak Village area of ​​Central Bangka. The geothermal geological structure of Terak is in the form of granite rocks with normal faults and horizontal faults or what is called the Pemali fault. The purpose of this research is to identify rock spreading on geothermal Terak based on magnetic anomaly. Magnetic data was processing by applied diurnal correction, IGRF correction, RTE (Reduce to the Equator) correction. Reginal dan residual anomaly was separation using upward continuation 350 m, 400 m, and 450 m. The result shown that rock spreading on geothermal Terak was consist by granite rock from Granite Klabat formation in north Mangkol Hill, sandstone from Tanjung Genting formation on West study area. Schist and phyllite was dominated on northeast and northwest area.